2008
DOI: 10.1560/ijc.48.3-4.169
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemistry of Liposomes

Abstract: This review aims to summarize the current state of research concerning the interaction of electrodes with liposomes suspended in solutions. Main attention is given to the complex mechanism of adhesion and spreading of liposomes on mercury electrodes. That mechanism can be studied with the help of chronoamperometry, where each adhesion‐spreading event appears as a capacitive current spike. Integration of these spikes produces charge versus time transients that can be modeled and simulated, revealing the details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 186 publications
(281 reference statements)
1
20
0
Order By: Relevance
“…8. The fit and the time constants show that the TMCL liposomes behave very similar to the previously studied DMPC, DOPC, and other liposomes [5][6][7].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…8. The fit and the time constants show that the TMCL liposomes behave very similar to the previously studied DMPC, DOPC, and other liposomes [5][6][7].…”
Section: Resultssupporting
confidence: 72%
“…The two pK a values of cardiolipins are such (pK a1 ≈2.8, pK a2 ≈7.5 and higher) that they exist under physiological conditions as mono-anions [2]. Recently, we have observed that mitochondria undergo on the surface of a mercury electrode an adhesion-spreading process [3] which resembles the adhesion-spreading processes which we have discovered when liposomes interact with a mercury electrode [4][5][6][7][8][9][10], and which have been also observed in case of thrombocyte vesicles [11]. In order to better understand the mitochondria experiments, and to expand our experience with the adhesion-spreading of liposomes, we have prepared unilamellar liposomes of the synthetic tetramyristoyl cardiolipin (TMCL) 1′,3′-bis[1,2-dimyristoyl-sn-glycero-3-phospho]-sn-glycerol (Fig.…”
Section: Introductionmentioning
confidence: 89%
“…Ionic interactions with phospholipids have been studied extensively using various biomimetic models such as supported bilayers [1][2][3] monolayers [4][5][6][7], vesicles [8,9] and tethered bilayers [10,11] and are important for investigating the effect of the ions on biomembrane function . Studies on the interaction of metal cations with dioleoyl phosphatidylcholine (DOPC) have shown that the strength of alkali metal cation binding to the head group follows the order: Li + >Na + >K + >Rb + >Cs + in accordance with the reverse Hofmeister series with no significant adsorption by anions excepting the larger Br À and I À [9,36].…”
Section: Introductionmentioning
confidence: 99%
“…The integrity of the mitochondrial membrane and changes in its composition play a crucial role in preventing or even triggering apoptosis. Here, we report that isolated functionally intact MI interact with the surface of a static mercury electrode in a way which is similar to the adhesion‐spreading of liposomes69 and thrombocytes,10 that is, they attach to the hydrophobic mercury surface and disintegrate by forming islands of adsorbed molecules. This attachment is caused by the hydrophobic interaction between mercury and the lipid chains,11 a topic with a long history and recently reviewed by Nelson 12.…”
mentioning
confidence: 86%